Plasmodium spp. In a captive raptor collection of a safaripark in northwest Italy. (February 2016) - Scaglione, F.E.; Cannizzo, F.T.; Chiappino, L.; Sereno, A.; Ripepi, M.; Salamida, S.; Manuali, E.; Bollo, E.
Abstract: Blood parasites infect all vertebrates (Clayton and Moore 1997). Avian malaria parasites ( Plasmodium spp., Plasmodiidae ) are cosmopolitan in their distribution and are responsible for severe diseases in domestic and wild birds. In September 2009, nine raptorial birds that either arrived recently or were maintained as permanent residents at the Safaripark Pombia (northwest Italy) showed loss of stamina, developing listlessness, anorexia and regurgitation. Within one month three animals died and were necropsied. Following the diagnosis of Plasmodium infection all other raptorial birds were treated: clinical improvement was observed in all birds, and blood smears made after one month resulted negative for parasites. Highlights: The paper describes an outbreak of malaria in captive raptors. Clinical findings and treatment are described. Macroscopical, histological, biomolecular and TEM techniques are reported. Hypothesis about the causes of the outbreak are provided.